Proceedings of the 53rd Annual Meeting of the Association for Computational Linguistics and the 7th International Joint Confere 2015
DOI: 10.3115/v1/p15-2080
|View full text |Cite
|
Sign up to set email alerts
|

User Based Aggregation for Biterm Topic Model

Abstract: Biterm Topic Model (BTM) is designed to model the generative process of the word co-occurrence patterns in short texts such as tweets. However, two aspects of BTM may restrict its performance: 1) user individualities are ignored to obtain the corpus level words co-occurrence patterns; and 2) the strong assumptions that two co-occurring words will be assigned the same topic label could not distinguish background words from topical words. In this paper, we propose Twitter-BTM model to address those issues by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…BTM directly models the generation of biterms (pairs of words) in the whole corpus. However, the assumption that pairs of cooccurring words should be assigned to the same topic might be too strong (Chen et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…BTM directly models the generation of biterms (pairs of words) in the whole corpus. However, the assumption that pairs of cooccurring words should be assigned to the same topic might be too strong (Chen et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…Recent work on learning user representations with multitask deep learning techniques (Li et al, 2015), suggests that learning a nonlinear mapping from observed views to the latent space can learn high quality user representations. One issue with GCCA is scalability: solving for G relies on an SVD of a large matrix that must be loaded into memory.…”
Section: Resultsmentioning
confidence: 99%
“…One related work was proposed by Zhang and Wang (2015), which employed bidirectional RN-N to learn patterns of relations from raw text data. Although bidirectional RNN has access to both past and future context information, the range of context is limited due to the vanishing gradient problem.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations